Crocidura shrews of tropical Africa : Phylogeography and morphological evolution - (:unkn) unknown (My University, 2023)
Speciation and diversification are slightly different concepts. While the first necessarily entails a rise in species richness, the latter can occur without speciation, and simply represents an increase in genetic or phenotypic diversity. Species richness is not always correlated with morphological diversity, and speciose clades may display huge discrepancies in the amount of morphological divergence. The Crocidura genus (Wagler, 1832) is a flamboyant example of high species richness and conservative morphology. With over 200 described species, it shows relatively little morphological differentiation, to the point that the exact number of species remains unknown, local species assemblages are extremely difficult to tell apart, and taxonomic revisions within the genus are frequent. « Crypsis » is used to qualify this lack of morphological differentiation, and relates to species that have remained undiscovered for lack of morphological divergence. Authors have argued that such species may represent ideal opportunities for the study of speciation and species diversification. In this thesis, we investigate the taxonomy and morphological variability within three species complexes, C. poensis, C. hildegardeae and C. hirta-flavescens, in an attempt to understand the speciation processes that occurred within these Crocidura shrews from tropical Africa. In the first chapter, our focus was set on the morphological evolution within C. poensis, in which we found no phylogenetic signal in skull morphology, entailing the existence of divergent selection in the West African lineages, which we attributed to parapatric speciation over an environmental gradient. In the second chapter, we describe a new species from West Africa, discovered through an integrative approach and the unusually high morphological variability within C. grandiceps. In the third chapter, we investigate the phylogeography of the C. hildegardeae species complex, in dire need of a taxonomic revisi
Keywords: African Research